2016
DOI: 10.21315/mjms2016.23.5.8
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of Iron Supplementation Consumption and its Related Factors in High School Students in Southeast Iran, 2015

Abstract: Background: This study aimed to estimate the prevalence of iron supplement consumption and its associated factors among high school students in Iran.Methods: A mixed-methods (quantitative-qualitative) study was conducted in Zahedan, southeast Iran, in 2015. The sample comprised 400 high school students from different areas of Zahedan who were randomly selected. A standard questionnaire and semi-structured interview were used to collect data in the quantitative and qualitative phases, respectively. The data wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 12 publications
2
14
0
1
Order By: Relevance
“…The results of a study by Kheirouri showed that only 62.3% of female students had taken iron supplements fully [17]. Another study on students conducted by khammarnia found that only 31% had fully taken iron supplements [18]. The results of Chauhan's research showed that out of 71.7% of students who had anemia, 89.5% did not take iron supplements [21].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The results of a study by Kheirouri showed that only 62.3% of female students had taken iron supplements fully [17]. Another study on students conducted by khammarnia found that only 31% had fully taken iron supplements [18]. The results of Chauhan's research showed that out of 71.7% of students who had anemia, 89.5% did not take iron supplements [21].…”
Section: Discussionmentioning
confidence: 99%
“…The most important reasons for not taking iron supplements from the viewpoint of the subjects, in order of priority, were as follows: bad taste of iron supplements, nausea after taking the supplements, no foreign iron supplements, no doctor prescription for the supplements, and no need for iron supplementation due to the lack of disease. In khammarnia's study, the most important reasons for not taking iron supplements have been identi ed, in order of priority, by students as follows: gastrointestinal problems, the in uence of friends and family, unwillingness to take and lack proper environmental conditions and facilities for taking supplements [18]. In the Sajna's research, the most important reasons for not taking iron supplements were reported as the reluctance to take iron pills, fear of problems raised by taking iron pills, stomach pain, parental unwillingness, taking another supplement, and vomiting [15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sistan and Baluchestan province, the widest province, is located in southeast of Iran with about 2.5 million people (7). According to integrated health indicators categorization, the province is the poorest region in Iran (12).…”
Section: Methodsmentioning
confidence: 99%
“…This is the reason for emphasis on the impoverishing effect of health expenditures (7). In this regard, the Iranian government tried to reduce the OOP payment by some reforms in financing of the health system, such as universal health insurance law, in the 4 and 5 year National Development Plans; however, they were not successful (5).…”
Section: Introductionmentioning
confidence: 99%